KURSI RODA DENGAN PENGENDALI BLUETOOTH SMARTPHONE ANDROID BERBASIS ARDUINO UNO - , RIO ASRULEOVITO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It has created wheel chair with bluetooth smartphone androidâs controller based arduino UNO who designed for make easier humanâs worked when use wheel chair flexibly and safely that the speed can be controlled in accordance with the user weight. This system consist with DC motor high torque, smartphone android, bluetooth HC-06, motorâs driver, and relayâs circuit that give direction and set the acceleration for DC motor, and microcontrollerâs system. The controller for this wheel chair it come from bluetooth smartphone android. The designed of wheel chairâs system use motorâs driver, relayâs circuit for give the directions and set the accelaration for DC motor and bluetooth HC-06, and softwareâs program. In this softwareâs program use Arduino UNO. The system of this wheel chair can be implemented by Arduino UNO. Androidâs smartphone is connected to bluetooth HC-06 that can communicate with Arduino UNO. If that devices can communicate each other then androidâs smartphone could send the command to the arduinoâs port is being connected with relayâs circuit and motorâs driver circuit. This motorâs driver circuit has function as give and set the DC motorâs accelaration with pwmâs value and other hand relayâs circuit has function as give the directions for DC motor on moving forward, backward, right, and left.